Staying fit: a must to be a successful Neurosurgeon - Thapa, Amit (Nepal Journal of Neuroscience, 2021)
When I decided to be a neurosurgeon, I was told that my professional life is going to be very short. At the start you would begin late as it takes long to be a competent one and later due to stress of life and work, soon you would feel either exhausted or due to physical issues would soon stop operating.Well this doomsday prediction for a career neurosurgeon may discourage new enthusiasts, the seasoned practitioner however knows what it takes to continue your career graph go up for long.Neurosurgeons need a blend of skills and personal qualities like a high degree of manual dexterity, good hand-eye co-ordination, excellent vision and visuo-spatial awareness, good organisational ability and effective decision-making skills. To achieve this professional requirement and to keep going strong, we need a healthy body and a problem-solving mind.